Analysis of The Contribution of Time, Income, and Family Labor Costs in Oil Palm and Rice Farming in Pino Raya Subdistrict - Oktapia, Hesvi Meska; Romdhon, Muhamad Mustopa; Windirah, Nola; Suryana, Anggita Tresliyana (Tarjih : Agribusiness Development Journal, 2025)
Oil palm and lowland rice farming systems rely on family labor to manage and maintain operations. This study analyzes the contribution of working time, income levels, and family labor costs in oil palm and lowland rice farming households in Pino Raya Subdistrict, South Bengkulu. The research employed a descriptive quantitative method using a survey approach through interviews with 25 respondents. Data analysis included the calculation of family labor contributions through work time contribution analysis (measured in person-days), income analysis (PD = TR - TC), and analysis of the contribution of family labor costs. The results showed that family labor contributed 60%, equivalent to 48.3 person-days per 3 months, in oil palm farming and 40%, or 31.9 person-days per 3 months, in lowland rice farming. The actual income from farming was IDR 6,721,168 per 3 months for oil palm and IDR 2,407,955 per 3 months for lowland rice. Family labor costs accounted for 58% of total farming costs in oil palm and 60% in lowland rice farming. This substantial contribution indicates that family members carry out most farming activities. Oil palm and lowland rice farming can generate higher income when family labor is optimally utilized, as it significantly contributes to overall farming costs. Therefore, it is recommended that farmers maintain and maximize the use of family labor to enhance cost efficiency and support production sustainability.